A ruthenium derivative of quercetin with enhanced cholesterol-lowering activity. Issue 46 (20th April 2016) - Cuccioloni, M.; Bonfili, L.; Mozzicafreddo, M.; Cecarini, V.; Pettinari, R.; Condello, F.; Pettinari, C.; Marchetti, F.; Angeletti, M.; Eleuteri, A. M.
Abstract : A ruthenium(ii ) p -cymene derivative of quercetin was synthesized and functionally tested for cholesterol-lowering ability via direct 3-hydroxy-3-methyl-glutaryl-CoA reductase (HMGR) inhibition. Abstract : A ruthenium(ii ) p -cymene derivative of quercetin was synthesized and functionally tested for cholesterol-lowering ability via direct 3-hydroxy-3-methyl-glutaryl-CoA reductase (HMGR) inhibition. Ruthenium complexation dramatically increased the inhibition potency of the parent quercetin toward HMGR, with a consequent enhancement of the cholesterol-lowering effect in hepatic cells.